2007
DOI: 10.1016/j.amepre.2007.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in Movies and Increased Smoking Among Young Adults

Abstract: Objective-This study assessed whether smoking in the movies was associated with smoking in young adults.Methods-A national web-enabled cross-sectional survey of 1528 young adults, aged 18-25, was performed between September and November 2005. Logistic regression and path analysis using probit regression were used to assess relationships between exposure to smoking in the movies and smoking behavior. Analysis was completed in December 2006.Results-Exposure to smoking in the movies predicted current smoking. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 35 publications
4
62
1
5
Order By: Relevance
“…Previous studies have established that tobacco advertising and imagery can help normalize tobacco use by making tobacco appear desirable and socially acceptable, which in turn may influence youth to use tobacco (National Cancer Institute, 2008). Previous research has also demonstrated that viewing smoking imagery in movies is associated with smoking initiation among adolescents (Dalton et al, 2003;Sargent et al, 2005) as well as established smoking behavior among young adults (Dalton et al, 2009;Song, Ling, Neilands, & Glantz, 2007). Although no studies have assessed the impact of YouTube videos on ST use, it is plausible that there is a similar relationship.…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies have established that tobacco advertising and imagery can help normalize tobacco use by making tobacco appear desirable and socially acceptable, which in turn may influence youth to use tobacco (National Cancer Institute, 2008). Previous research has also demonstrated that viewing smoking imagery in movies is associated with smoking initiation among adolescents (Dalton et al, 2003;Sargent et al, 2005) as well as established smoking behavior among young adults (Dalton et al, 2009;Song, Ling, Neilands, & Glantz, 2007). Although no studies have assessed the impact of YouTube videos on ST use, it is plausible that there is a similar relationship.…”
Section: Introductionmentioning
confidence: 82%
“…Po rezultatima ispitivanja mladih ljudi iz drugih delova sveta cigarete svakodnevno puši četvrtina studentske populacije oba pola [12,[20][21]. Sprovedeno istraživanje je pokazalo još veću učestalost pušača u ovoj populacionoj grupi, obzirom da je detektovano 32,8% pušača, što zabrinjava budući da se radi o studentima medicinske grupacije fakulteta od kojih se očekuje razvijena svest o štetnosti duvana.…”
Section: Diskusijaunclassified
“…Evidence used by the NCI to conclude that exposure to movie smoking causes adolescent smoking was not based upon simple trend analysis, as suggested, but on a broad collection of evidence-including a historical analysis; content analyses of smoking in movies; exposure assessments among adolescents; and the convergence of results from carefully conducted experiments, qualitative investigations and epidemiological studies of adolescent attitudes and behavior involving thousands of individuals (now from several countries). Additional cross-sectional [4][5][6][7] and longitudinal [8][9][10][11] studies, some showing that positive tobacco attitudes mediate the effect of movies on behavior [7,8,12], and all published since the NCI monograph was written, bolster the causal conclusion.…”
Section: Evidence-based Policy: An R-rating For Movies With Smokingmentioning
confidence: 99%